Pelatihan Pemanfaatan Media Sosial Instagram Untuk Memperluas Media Komunikasi dan Informasi Pada TPA/Majelis Ta’lim Faizul Haq - Syahriani riani; tri santoso; Sulistianto Sw; Ardian Dwi Praba (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The condition of the Covid-19 pandemic has made various sectors of life stopped or temporarily stagnate, it can be seen in terms of religious life, especially those that have been affected. To prevent the spread of the COVID-19 virus, government officials have advised religious people to worship at home. This condition also affects the congregation or the students of the Faizul Haq Ta'lim Council, where the congregation or students who carry out activities in this Assembly experience a decline and continue to decrease than usual and the distribution of knowledge or da'wah to the congregation or students also cannot be delivered optimally. On the basis of these problems, this community service is carried out to serve as a medium of communication and information regarding the activities that exist in this Assembly, rekindling the dissemination of da'wah and the provision of knowledge in the Faizul Haq Ta'lim Council by the board management or teachers so that it can be conveyed to the congregation or students and the wider community. This community service is carried out online using a laptop that has the Zoom application media installed in it. In this community service, we equip the students (children or teenagers) of the Faizul Haq Ta'lim Council, to be able to create a virtual community using Instagram social media which contains da'wah content or information and can perpetuate Islamic religious activities. others, so that it is widely spread to the community, so that the knowledge conveyed in da'wah or other Islamic religious activities can become knowledge for the wider community. In addition, we also equip these students (children and teenagers) in managing this Instagram virtual community account, so that they can become virtual accounts that can be trusted by their followers.